Cereal Bars Flavored with Fish Protein Concentrate from Different Species. Issue 1 (2nd January 2020) - Vitorino, Kelly Cristina; Chambo, Ana Paula Satório; Coradini, Melina Franco; Matiucci, Marcos Antonio; Graton Michka, Jane Martha; Goes, Elenice Souza dos Reis; Gonçalves, Alex Augusto; Souza, Maria Luiza Rodrigues de
ABSTRACT: The objective of this study was to develop and evaluate the microbiological, centesimal composition, and sensory characteristics of cereal bars with fish protein concentrate (FPC) inclusion. Four formulations of cereal bar (CB) were developed with 10% FPC: Treatment 1 (without FPC addition), Treatment 2 (Nile tilapia protein concentrate inclusion), Treatment 3 (Nile tilapia and salmon protein concentrate inclusion), and Treatment 4 (Nile tilapia and tuna protein concentrate inclusion). The microbiological analysis was within the microbiological standards for human consumption. The inclusion of FPC did not influence ( p > .05) the content of moisture, protein, lipids, carbohydrates, and calorie value. Only the ash content had higher levels (2.50 to 3.45%). The sensory attributes evaluated and the purchase intent did not differ between treatments. Our results demonstrate that the inclusion of 10% protein concentrates from tilapia, salmon, and tuna byproducts is effective for increasing the mineral matter of cereal bars without affecting their sensory profile.